The Effect Entrepreneurship Education and Subjective Norm on Biology Students’ Self-Efficacy in Entrepreneurial - Agus Muliadi; Baiq Mirawati; Saiful Prayogi (IKIP Mataram, 2021)
This study aims to determine the effect of entrepreneurship education and subjective norms on students’ self-efficacy in the field of entrepreneurship. This study is an exploratory research with 35 students’ of biology education as research subjects. The research instrument used is a closed questionnaire with answers that are degraded according to the Likert scale which has been declared valid and reliable to use. Analysis of research data used is descriptive statistics and inferential statistics with multiple linear regression test at a significance level of 5%. The results of the study show that (1) students' perceptions of entrepreneurship education have an average of 3.15 in the Good category, subjective norms of 3.06 in the Good category, and self-efficacy of 3.12 in the Good category; (2) There is an effect of entrepreneurship education and subjective norms on students’ self-efficacy with an F value of 11.713 and a significance value (p) <0.05; (3) Entrepreneurship education and subjective norms simultaneously affect the self-efficacy of biology students’ by 42.3% and the rest are influenced by other variables or factors.